Exploring Alienable—Inalienable Possessions in Yaben - Mayor, Infak Insaswar; Sawaki, Yusuf Willem (Masyarakat Linguistik Indonesia, 2025)
This article discusses structural and semantic properties of possessive constructions in Yaben, a Papuan language of Trans New Guinea spoken in the South of Bird’s Head of New Guinea along the Kaibus River, South Sorong Regency. The purpose of the study is to explore alienable-inalienable possessive distinction in structural and semantic expressions in Yaben. In doing this research, the descriptive method was used, and the data were taken with an elicitation technique. The typological approach is also used as a comparative analysis between Yaben and other Papuan and Austronesian languages in the area. The finding of the study shows that the distinction between alienable and inalienable possessions is obvious at the structural and semantic levels. Two grammatical properties are used to indicate alienable and inalienable possessions, which are morphological and syntactic (phrasal) constructions. The morphological construction and noun-noun juxtaposition are used to mark inalienable nouns: kinship terms, body parts, common nouns, and associative nouns; while the possessive marker migine ‘POSS’ linking the possessor and the possessed noun functions to indicate the alienable noun: whole part relational nouns. Yaben shows a prototypical alienable-inalienable possessive distinction, as do other Papuan and Austronesian languages of Papua.